Оптимизация системы подчиненного регулирования скорости на максимум добротности при заданых запасах устойчивости в главном и подчиненном контурах - Литвиненко, Дмитрий Григорьевич (НТУ "ХПИ", 2010)
In article possibility of the further search of optimum balance of good quality and a stock of stability of repeatedly integrating systems at the expense of the account of regulators parameters influence of internal and external contours is considered.
Optimization of speed subordinated regulation systems on the good quality maximum at setting stability stocks in the main and subordinate contours
Keywords: многократно интегрирующая система; система электромеханическая; баланс; оптимум симметричный; диаграмма качества управления; контур тока